Designing unemployment benefits in developing countries - David A. Robalino (IZA World of Labor, 2014)
In reforming unemployment benefit systems, the policy debate should be on the appropriate level of benefits, the subsidies needed for people who cannot contribute enough, and how to finance the subsidies, rather than on whether unemployment insurance or individual unemployment savings accounts are better. Unemployment insurance finances subsidies through implicit taxes on savings, while individual savings accounts with solidarity funds finance subsidies through payroll taxes. Taxes on certain consumption goods and real estate could be considered as well and could be less distortionary.
Keywords: J6; J65; 330; unemployment benefits; risk-pooling; savings accounts; labor market